Numerical model for the cracking behavior of heterogeneous brittle solids subjected to thermal shock. (February 2016) - Tang, S.B.; Zhang, H.; Tang, C.A.; Liu, H.Y.
Highlights: A thermo-mechanical coupling model is developed to study the cracking of heterogeneous brittle solids subjected to thermal shock. The higher the initial temperature of the brittle solid, the larger the number of the initiated cracks is and the narrower the spacing between the cracks becomes. The initiated cracks can be classified into different hierarchical levels according to their length. The cracking pattern in the heterogeneous brittle solid depends on its thermal conductivity when quenching is applied. Abstract: A finite element based numerical model is developed to simulate the thermal cracking behavior of brittle solids subjected to thermal shock. The heterogeneity of the brittle solids at mesoscopic level is taken into account using the Weibull distribution. Furthermore, the cracking behavior of meso-element is modeled using continuum damage mechanics. The finite element method (FEM) is used to obtain thermal stress distribution, and then damage threshold is determined by the maximum tensile stress criterion. In the present work, the cracking behavior, including the initiation and propagation of microcracks, and the formation of approximately equally spaced surface cracks, are well captured by the numerical model. Furthermore, the impact of thermal conductivity on the cracking pattern of the heterogeneous brittle solids is also discussed in this study. The numerical simulation results are found to be consistent with the experimental observations in the literature, which indicates that the proposed numerical model is a potentially powerful tool to study the cracking behavior of the heterogeneous brittle solids subjected to thermal shock. Graphical abstract: